SURGICAL CORRECTION OF ISTHMIC CERVICAL INSUFFICIENCY IN NON-PREGNANT WOMEN: A CLINICAL CASE - A. G. Yashuk; R. A. Naftulovich; R. M. Zainullina; E. M. Popova; O. V. Yakovleva (IRBIS LLC, 2018)
Clinicians often see a recurrent miscarriage caused by isthmic cervical incompetence. Today, obstetric pessaries and surgical sutures are widely used to correct cervical incompetence during pregnancy. The occurrence rate of this abnormality continues to rise, which emphasizes the need to diagnose and correct cervical incompetence prior to the upcoming pregnancy. In the available literature there is little information about the «hidden» defects of the cervix that can lead to miscarriage in the I-III trimesters of pregnancy. Here we present a case of two different pregnancy outcomes in a single patient with cervical incompetence before and after surgical correction of the cervix by the LASH procedure. The present case supports the importance of surgical correction of cervical incompetence in non-pregnant women.